2015
DOI: 10.1007/s11356-015-5361-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of xylo-oligosaccharides in protection against salinity-induced adversities in Chinese cabbage

Abstract: Soil salinity is a stringent abiotic constraint limiting crop growth and productivity. The present study was carried out to appraise the role of xylo-oligosaccharides (XOSs) in improving the salinity tolerance of Chinese cabbage. Salinity stress (0.5% NaCl solution) and four levels (0, 40, 80, 120 mg L(-1)) of XOSs were imposed on 20-day-old plants cultured under controlled conditions. Salinity stress decreased the aboveground fresh biomass, photosynthesis, transpiration rate, stomatal conductance, internal CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…and non-enzymatic (GSH, Vc, Ve etc.) antioxidants, is regarded to overcome the cascades of uncontrolled oxidation and protect the plant cells from ROIs-induced oxidative damage ( Foyer and Noctor, 2005 ; Gill and Tuteja, 2010 ; Anjum et al, 2015 ; Chen et al, 2015 ). The SOD plays a key part in catalyzing the dismutation of , while CAT, POD, and GPX contribute in scavenging of H 2 O 2 ( Gill and Tuteja, 2010 ; Anjum et al, 2015 ; Fahad et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and non-enzymatic (GSH, Vc, Ve etc.) antioxidants, is regarded to overcome the cascades of uncontrolled oxidation and protect the plant cells from ROIs-induced oxidative damage ( Foyer and Noctor, 2005 ; Gill and Tuteja, 2010 ; Anjum et al, 2015 ; Chen et al, 2015 ). The SOD plays a key part in catalyzing the dismutation of , while CAT, POD, and GPX contribute in scavenging of H 2 O 2 ( Gill and Tuteja, 2010 ; Anjum et al, 2015 ; Fahad et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome the excessive ROIs-generation, the plants possess a highly sophisticated and efficient antioxidative defense system. The disruption of cellular homeostasis and stress-induced damages are mitigated by the action of various enzymatic (superoxide dismutase, SOD; catalase, CAT; peroxidase, POD; glutathione peroxidase, GPX; glutathione reductase, GR; glutathione-S-transferase, GST) and non-enzymatic (glutathione, GSH; ascorbic acid or vitamin C, Vc; α-tocopherol or vitamin E, Ve; and carotenoids) antioxidants ( Foyer and Noctor, 2005 ; Gill and Tuteja, 2010 ; Anjum et al, 2015 ; Chen et al, 2015 ). In plants, the levels of ROIs are regulated by the rate of their production/generation and the extent of neutralization by enzymatic and/or non-enzymatic antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Plants possess a highly efficient and sophisticated antioxidative defense system to control the overproduction of ROS ( Hussain et al, 2016 ). The ROS-induced damages and disruption of cellular homeostasis are alleviated by the action of different enzymatic (e.g., catalase, CAT; superoxide dismutase, SOD; peroxidase, POD; glutathione reductase, GR; glutathione peroxidase, GPX) and non-enzymatic (e.g., ascorbic acid, carotenoids, α-tocopherol, and glutathione content) antioxidants ( Gill and Tuteja, 2010 ; Chen et al, 2016 ; Hussain et al, 2016 ). In plants, the levels of ROS are regulated by their production rate as well as the extent of their detoxification by enzymatic and/or non-enzymatic antioxidant systems.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these conditions, plants have evolved the antioxidant defense systems including antioxidant enzymes (e.g., superoxide dismutase, SOD; catalase, CAT; peroxidase, POD) and non-enzymatic antioxidants (e.g., ascorbic acid, AsA; glutathione, GSH) which may neutralize or counteract the harmful effects of ROS and protect the plants from oxidative stress ( Foyer and Noctor, 2005 ; Gill and Tuteja, 2010 ; Anjum et al, 2015 ; Chen et al, 2015 ). Previously, it has been found that the activities of antioxidants under chilling stress were correlated with stress tolerance and chilling-tolerant maize ( Hodges et al, 1997 ; Taka, 2004 ), cucumber ( Kang and Saltveit, 2002 ), and rice ( Kang and Saltveit, 2002 ; Huang and Guo, 2005 ) cultivars had higher anti-oxidation activities.…”
Section: Introductionmentioning
confidence: 99%